Iterative development of engineering in school teaching capacities in Danish primary and lower secondary schools. - Peer Schrøder Daugbjerg,; Martin Krabbe Sillasen (JETEN, 2019)
We have developed and performed a Teacher Professional Development (TPD) programme for introducing and implementing engineering in primary and lower secondary school in Denmark. Engineering is a newcomer in Danish schools, and we only had fuzzy ideas about how to introduce it when we started. We therefore designed